Renal Heme Oxygenase-1 Induction with Hemin Augments Renal Hemodynamics, Renal Autoregulation, and Excretory Function. (8th February 2012) - Botros, Fady T.; Dobrowolski, Leszek; Navar, L. Gabriel
Abstract : Heme oxygenases (HO-1; HO-2) catalyze conversion of heme to free iron, carbon monoxide, and biliverdin/bilirubin. To determine the effects of renal HO-1 induction on blood pressure and renal function, normal control rats (n = 7 ) and hemin-treated rats (n = 6 ) were studied. Renal clearance studies were performed on anesthetized rats to assess renal function; renal blood flow (RBF) was measured using a transonic flow probe placed around the left renal artery. Hemin treatment significantly induced renal HO-1. Mean arterial pressure and heart rate were not different (115 ± 5  mmHg versus 11 2 ± 4  mmHg and 331 ± 16 versus 346 ± 10  bpm). However, RBF was significantly higher (9.1 ± 0.8 versus 7.0 ± 0.5  mL/min/g, P < 0.05 ), and renal vascular resistance was significantly lower (13.0 ± 0.9 versus 16.6 ± 1.4 [mmHg/(mL/min/g)], P < 0.05 ). Likewise, glomerular filtration rate was significantly elevated (1.4 ± 0.2 versus 1.0 ± 0.1  mL/min/g, P < 0.05 ), and urine flow and sodium excretion were also higher (18.9 ± 3.9 versus 8.2 ± 1.0  μ L/min/g, P < 0.05 and 1.9 ± 0.6 versus 0.2 ± 0.1  μ mol/min/g, P < 0.05, resp.). The plateau of the autoregulation relationship was elevated, and renal vascular responses to acute angiotensin II infusion were attenuated in hemin-treated rats reflecting the vasodilatory effect of HO-1 induction. We conclude that renal HO-1 induction augments renal function which may contribute to the antihypertensive effects of HO-1 induction observed in hypertension models.